MODULATED THERMOCONVECTIVE WAVES IN THE EARTHundefinedS LITHOSPHERE - Birger B.I. (My University, 1998)
For flows associated with small strains, the rheology of rocks is described by a linear integral (having a memory) law, which reduces to the Andrade law in the case of constant stresses. The continental lithosphere with such a rheology is overstable. Thermoconvective waves propagating through the lithosphere without attenuation have a period of about 200 Ma and a wavelength of the order of 400 km. A pointwise perturbation of the initial temperature in the lithosphere excites amplitude-modulated thermoconvective waves (wave packets). When the initial perturbation occupies a finite area, thermoconvective waves move outside from this area and thermoconvective oscillations (standing waves) are settled within the area. Thermoconvective waves induce oscillations of the Earth'' surface, accompanied by sedimentation and erosion, and can be viewed as a mechanism for the distribution of sediments on continental cratons.
Keywords: THERMOCONVECTIVE WAVES; EARTH''S LITHOSPHERE; SEDIMENTS; RHEOLOGY OF ROCKS